2020
DOI: 10.1021/acssuschemeng.0c03685
|View full text |Cite
|
Sign up to set email alerts
|

Biophenol-Mediated Solvent-Free Synthesis of Titanium Silicalite-1 to Improve the Acidity Character of Framework Ti toward Catalysis Application

Abstract: Although titanium silicalite-1 (TS-1) with enhanced Lewis acidity can show significant catalytic functionality, the effective and green synthesis of such a TS-1 zeolite still remains a challenge. In this work, a biophenol-mediated solvent-free strategy is adopted to synthesize bio-TS-1 with an improvement of acidity character. Systematic characterizations are devoted to inspect the structural and acidic properties of the as-prepared bio-TS-1. Furthermore, density functional theory simulations are carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Compared with conventional synthesis, solvent-free synthesis of zeolites has obvious advantages, such as high zeolite yields, high autoclave utilization, significantly reduced pollutants, reduced energy consumption, simple synthesis processes, and significantly reduced reaction pressures (Meng and Xiao, 2014). Subsequently, it was also successful to synthesize TS-1 zeolite using this method (Zhu et al, 2015;Cui et al, 2017;Fu et al, 2020;Wang et al, 2020;Liu et al, 2022). Zhu et al (2015) reported the synthesis of TS-1 zeolite using fumed silica, titanium sulfate, TPAOH and zeolite seeds as raw materials under solvent-free conditions.…”
Section: Solvent-free Synthesismentioning
confidence: 99%
“…Compared with conventional synthesis, solvent-free synthesis of zeolites has obvious advantages, such as high zeolite yields, high autoclave utilization, significantly reduced pollutants, reduced energy consumption, simple synthesis processes, and significantly reduced reaction pressures (Meng and Xiao, 2014). Subsequently, it was also successful to synthesize TS-1 zeolite using this method (Zhu et al, 2015;Cui et al, 2017;Fu et al, 2020;Wang et al, 2020;Liu et al, 2022). Zhu et al (2015) reported the synthesis of TS-1 zeolite using fumed silica, titanium sulfate, TPAOH and zeolite seeds as raw materials under solvent-free conditions.…”
Section: Solvent-free Synthesismentioning
confidence: 99%
“…Besides, it is related to the formation of Ti-OOH active intermediates during epoxidation, which can catalyze propylene epoxidation to PO. 11 Recently, researchers have attempted to introduce trivalent metals such as Al, Fe, etc. into TS-1 to form bifunctional catalysts, which has shown that the introduction of trivalent metals increases the acidity of TS-1 and contributes to the ring-opening reaction of PO.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic epoxidation process involves first reaction of H 2 O 2 with the isolated Ti 4+ to generate active intermediates (Ti-OOH), and subsequent reaction of these Ti-OOH species with propylene to transfer the O atom of the Ti-OOH to oxidize propylene, thus forming PO and H 2 O. 5,6 Simultaneously, the by-products of PG, PPM and SPM are formed by the solvolysis of PO, i.e., the hydrolysis and alcoholysis of PO between H 2 O and CH 3 OH, respectively (as illustrated in Scheme 1). Indeed, previous studies found that the epoxidation process and the side reactions were determined as a consecutive-parallel reaction scheme by propylene synthesis experiments and separate experiments with PO and CH 3 OH and H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic epoxidation process involves first reaction of H 2 O 2 with the isolated Ti 4+ to generate active intermediates (Ti–OOH), and subsequent reaction of these Ti–OOH species with propylene to transfer the O atom of the Ti–OOH to oxidize propylene, thus forming PO and H 2 O. 5,6 Simultaneously, the by-products of PG, PPM and SPM are formed by the solvolysis of PO, i.e. , the hydrolysis and alcoholysis of PO between H 2 O and CH 3 OH, respectively (as illustrated in Scheme 1).…”
Section: Introductionmentioning
confidence: 99%